The Challenges of Industry 4.0 Technology Adoption in Texas Instruments Electronics in Melaka - Lim Wey Nan; Siti Norziah Ismail (Research in Management of Technology and Business, 2024)
Industry 4.0 refer to the convergence of operational technology and information to observe mechanisms in manufacturing and use data to make predictive, perfective, and adaptive decisions to reduce operational costs. Malaysia has less modern technology than other affluent countries. This is due to a lack of information and awareness of Industry 4.0. The annual report of TI shows that rapid technical advancement in markets may result in shorter product life cycles and lower average selling prices for the products. The operational success influenced in part by our capacity to invent, manufacture, and distribute new items in a timely and cost-effective manner. The objective of this study is to identify the challenges of Industry 4.0 technology adoption and investigate the strategies to improve the implementation of Industry 4.0 technology in Texas Instruments company in Melaka. This study has been used qualitative method (interview session) to gather data from targeted respondents which are manager and engineer in Texas Instrument company who implement Industry 4.0. Here, semi-structured interviews using Google Meet act as the main tool for collecting data. The findings in this research expose the company should be take time to understand or plan out the procedure of IR 4.0 technology and take time to implement due to most of machines are used in production. However, they able to experiment with specific Industry 4.0 technologies on more complicated tasks. Besides, this research is only conducted at one company only which is in the Texas Instrument Electronics company in Melaka, Malaysia. Future research can expand to other companies to obtain more accurate data.